2014
DOI: 10.3732/ajb.1400125
|View full text |Cite
|
Sign up to set email alerts
|

Coordination and plasticity in leaf anatomical traits of invasive and native vine species

Abstract: The linkages demonstrated in the study between stomatal complex/gross anatomy and physiology are scarce in the ecological literature of plant invasiveness, but the findings suggest that leaf anatomical traits need to be considered routinely as part of weed species assessment and in the worldwide leaf economic spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
(106 reference statements)
2
15
0
3
Order By: Relevance
“…The relationship between these two features is still not too well understood, however. Godoy et al (2012) and Osunkoya et al (2014) found that invasive plant species had, albeit to a limited extent, higher integration than related native species, and Colautti and Barrett (2011) found considerable integration in the invasive plant Lithrum salicaria L., as strong genetic correlations among life-history traits constrained the divergence among invading subpopulations of this species.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between these two features is still not too well understood, however. Godoy et al (2012) and Osunkoya et al (2014) found that invasive plant species had, albeit to a limited extent, higher integration than related native species, and Colautti and Barrett (2011) found considerable integration in the invasive plant Lithrum salicaria L., as strong genetic correlations among life-history traits constrained the divergence among invading subpopulations of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Сильвопратанты равнин (группа III) отличаются от видов сухих склонов, степей и лугов (группа V) меньшими значениями диаметра черешка розеточного листа (p<0.00002) в 0,3 раза, m 1 /m (p<0.0002) в 0,9 раза, большими значениями индекса стеблевого листа (I l ) (p<0.004) в 1,1 раза, m 1 /S (p<0.04) в 1,2 раза, удельной площади стеблевого листа (SLA) (p<0.00001) в 1,3 раза. На основании того, что удельная площадь листа (SLA) связана с рядом важных адаптивных признаков [OSUNKOYA et al, 2014], предполагаем, что в условиях интродукции у сильвопратантов накапливается воды на единицу площади розеточного листа больше по сравнению с альпийцами и сильвантами, но по сравнению с первыми эффективность ее использования (WUE) в весенний период ниже, по сравнению со вторыми выше.…”
Section: сравнение эколого-морфологических параметров листа разныunclassified
“…На основании того, что сильванты отличаются от группы V также большей удельной площадью листа (SLA) разных формаций, которая отрицательно связана с устьично-поровым индексом (SPI) [OSUNKOYA et al, 2014], предполагаем, что лесные виды адаптировались к аридным условиям интродукции благодаря высокой эффективности использования энергии фотосинтеза (PEUE). Длинный черешок розеточного листа и большая площадь листа разных формаций лесных видов рода Campanula обеспечивают оптимальное улавливание света под пологом в естественных местах их произрастания.…”
Section: сравнение эколого-морфологических параметров листа разныunclassified
See 1 more Smart Citation
“…Other studies have demonstrated that invasive species show higher trait integration than non-invasive ones (Osunkoya et al 2014;Luo et al 2015). Trait integration (or trait coordination) is an estimation of the number of trait pairs that are significantly correlated in their response to changes in environmental conditions.…”
mentioning
confidence: 99%